Enviro-exergy sustainability analysis of boiler evolution in district energy system. (15th January 2017) - Compton, M.; Rezaie, B.
Abstract: Investigations into energy resources are important from the point of energy sustainability. The principal objective of this study is to investigate the evolution of the operating boilers at the University of Idaho (UI) district energy plant through an exergy analysis. The biomass boiler uses western red cedar chips from nearby lumber mills and provides 95% of the steam requirements of the main campus of UI in Moscow, ID, USA. Thermodynamic analysis reveals a thermal efficiency of 76% and an exergy efficiency of 24% for the biomass boiler. A combustion model is developed to determine the primary emissions products of both the bone dry wood chips and natural gas fuels. CO2 comprises 26% of the bone dry biomass emissions and 8% of the natural gas emissions products. Testing results of the biomass boiler exhaust stack show CO2 emissions of 14% when an average moisture content of 33% is accounted for. An overview of the evolution of the energy plant is discussed, showing the generational differences in each boiler. By using a biomass fuel source, the cost per 1000 kg of steam produced is on average 63% lower than using natural gas, resulting in savings of over $1 million annually. Highlights: Exergy efficiency comparison of biomass and natural gas boilers. Moisture content in biomass reduces average heating value and exergy efficiency. Local sustainable energy sources can result in economic savings over fossil fuels. Older boilers can have comparable efficiencies with newer ones after improvements.